الميول المهنية حسب نظرية هولاند لدى تلاميذ السنة الأولى ثانوي المنتقلين آليا في ضل جائحة كورونا كوفيد-19 - العقون، سوسن (جامعة الوادي university of Eloued, 2021)
الملخص: هدفت الدراسة الحالية الى معرفة طبيعة الميول المهنية لدى تلاميذ السنة الأولى ثانوي المنتقلين آليا حسب نظرية هولاند، والتحقق من دلالة الفروق في هذه الميول حسب الجنس والشعبة. وتم الاعتماد على المنهج الوصفي بأسلوبيه الاستكشافي والسببي المقارن. وتم إجراء الدراسة على (55) تلميذ وتلميذة من تلاميذ السنة الأولى ثانوي المنتقلين أليا من الجذعين المشتركين من ثانويات كل من بلدية الدبيلة (ثانوي محمد آل خليفة/ثانوية شعباني عباس)، وببلدية حساني عبد الكريم (ثانوية ديدي صالح/ثانوية بدر الدين صالح) بولاية الوادي. -واستخدم في هذه الدراسة مقياس مستوى الميول المهنية "لجون هولاند" لصاحبه " البراشدي2009. -أما البيانات فقد عولجت بإستخدام برنامج لحزمة الإحصائية SPSS للمعالجة الإحصائية والمتمثلة في حساب التكرارات والنسب المئوية لتساؤل العام للدراسة، واستعمال اختبار "كا2" لفرضيات الدراسة. -وقد توصلت الدراسة الى نتائج التالية: أن الميول المهنية مختلفة بين تلاميذ السنة الأولى ثانوي المنتقلين آليا حسب نظرية هولاند حيث برزت ثلاث أنماط رئيسية كانت هي الأعلى في هذه الدراسة وهما على الترتيب التالي: النمط الاجتماعي بنسبة29.09 %، والنمط الواقعي بنسبة 23.64 %، والنمط الإستقصائي بنسبة 20 %، أما بالنسبة الى النمط الغير ناضج قدرت نسبته بـ 12.7 %، وأن اختلاف هذه الميول هو إختلاف حقيقيا ودال إحصائيا. - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين الذكور والإناث من تلاميذ السنة الأولى ثانوي المنتقلين آليا في أنماط مقياس الميول المهنية حسب نظرية هولاند. - لا يوجد فروق دالة إحصائي عند مستوى الدلالة ( ) بين تلاميذ السنة الأولى ثانوي المنتقلين آليا في أنماط مقياس الميول المهنية تبعا للشعبة الدراسية (العلمية/ الأدبية). فرنسية أو انجلزية The current study aimed to know the nature of the professional tendencies of the first year secondary school students who transferred automatically according to Holland's theory, and to verify the significance of the differences in these tendencies according to gender and division. The descriptive approach was relied on with its exploratory and causal comparative methods. The study was conducted on (55) male and female students of the first year of secondary school who transferred automatically from the two common branches from the secondary schools of each of the municipalities of Al-Dibila (Mohammed Al Khalifa High School / Shabani Abbas High School), and the municipality of Hassani Abdul Karim (Didi Saleh High School / Badr Al-Din Saleh High School). El ouadi State. - In this study, the scale of the professional tendencies of "John Holland" with its author "Al-Barashdi 2009" was used. -As for the data, they were treated using the SPSS program for statistical treatment, which is to calculate the frequencies and percentages of the general question of the study, and using the "Ka2" test for the study's hypotheses. The study reached the following results: - The professional tendencies are different among the first-year secondary school students who are automatically transferred according to Holland’s theory, where three main patterns emerged that were the highest in this study, and they are in the following order: the social pattern by 29.09%, the realistic pattern by 23.64%, and the investigative pattern by 20%. Regarding the immature pattern, its percentage was estimated at 12.7%, and that the difference in these tendencies is a real and statistically significant difference. ( ) -There are no statistically significant differences at the level of significance between males and females of the first-year secondary school students who are transferred automatically in the patterns of the professional tendencies scale according to Holland's theory. ( ) - There are no statistically significant differences at the level of significance among the students of the first year of secondary school who are transferred automatically in the patterns of the professional tendencies scale according to the academic division (scientific/literary).
دراسة ميدانية بثانويات كل من بلديتي الدبيلة وحساني عبد الكريم
مذكرة ماستر علم الاجتماع تخصص إرشاد وتوجيه
Keywords: الميول المهنية; inclinations professionnelles; professional inclinations